PENGARUH KUALITAS LAYANAN, KEMUDAHAN, DAN EMOTIONAL FACTOR TERHADAP WORD OF MOUTH DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi pada Pelanggan OLX) - KUSUMA NUGROHO, WAHYU (Jurnal Ilmu Manajemen (JIM), 2017)
Internet usage can be used as a means commerce of online called e-commerce (electronic commerce). The rapid development of E-commerce causing rivalry which eventually led the actors of E-commerce itself with OLX as a market leader in the category of selling online site. The aim of this study are to analyze and discuss the influence of the service quality, eases, and emotional factor on the word of mouth and satisfaction as an intervening variable. Satisfaction is measured by several drivers of satisfaction to determine the extent of word of mouth made by OLX customer. Respondents in this study are college student aged 20-24 years who have made a purchase in OLX at least twice with the last purchase is in the last two month. The sampling method is nonprobability sampling and the sampling technique using snowball sampling. The sample used is 220. Data collection techniques which is used in this study is an online questionnaire. The data were analyzed by using path analysis with AMOS program. The result of this study indicates that the service quality, ease, and emotional factor have a significant effect on satisfaction. Ease and emotional factor significantly influence word of mouth, while the service quality doesn’t effect word of mouth. The result of this study also showed that the service quality, ease, and emotional factor has indirect effect on word of mouth and through satisfaction as mediating variables. But the first mediating test (service quality) fully proved while the ease and emotional factors are partially proved. Keywords: service quality, ease, emotional factor, customer satisfaction, word of mouth